The Effectiveness of Using Google Form Assisted Student Worksheets in Increasing Learning Independence and Student Mathematic Communication Skills in SMP Negeri 5 Langsa - Hanafiah Hanafiah; Roni Priyanda; Nishbah Fadhelina (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Changes in the way students learn which until now have decreased, especially in communicating story problems in the form of mathematics. This problem is increasingly seen when students have to study remotely due to the Covid-19 pandemic, the limited knowledge of parents or guardians of students at home who do not all go to school adds to these problems are more complete, so we need a method or method that can increase interest in learning and communication skills. Mathematical students. So that the goal in this study is to analyze whether the use of google form assisted student worksheets can increase student learning independence, and to accurately determine the level of mathematical communication skills of students taught using google form assisted student worksheets during the Covid-19 pandemic. The subjects in this study were all students of SMP Negeri 5 Langsa class VIII, totaling 87 students, and the object of this study was the effectiveness of using google form assisted student worksheets. This type of research is descriptive qualitative with qualitative and quantitative approaches. The results in this study indicatethat there are 7 students (8.05%) the level of student independence is high, and 71 students (81.61%) are classified as moderate and 9 students (10.34%) are classified as low. For the mathematical communication skills of students who are taught using LKS media assisted by google form is classified as better compared to students before being taught with LKS media assisted by google form, overall students can solve problems properly, correctly and completely.